A chemically bonded and plasmonic Z-scheme junction for high-performance artificial photosynthesis of hydrogen peroxide. Issue 3 (4th January 2023) - Shao, Teng; Chang, Yuan; Li, Zhuwei; Song, Yurou; Jin, Dingfeng; Gao, Junfeng; Sun, Licheng; Hou, Jungang
Abstract : Chemically bonded and plasmonic Z-scheme junction as a model material was produced by in situ assembly of nonstoichiometric W18 O49 (WO) onto two-dimensional carbon nitride nanosheets (CNs) for high-performance artificial photosynthesis of H2 O2 . Abstract : Artificial photosynthesis has been regarded as a promising solution for the clean, sustainable, and efficient production of hydrogen peroxide (H2 O2 ). However, rigorous regulation of light absorption, charge transfer, and surface kinetics is significant for catalytic performance. As a proof of concept, we report a chemically bonded and plasmonic Z-scheme junction as a model material prepared by the in situ assembly of nonstoichiometric W18 O49 (WO) onto two-dimensional carbon nitride nanosheets (CNs) for high-performance artificial photosynthesis of H2 O2 . Notably, this typical Z-scheme photocatalyst exhibits the highest H2 O2 generation rate of 732.4 μmol g −1 h −1, higher than that of individual catalysts, even maintaining 140.5 μmol g −1 h −1 under broad-spectrum response irradiation ( λ > 700 nm). From the analysis of experimental characterization and density functional theory calculations, the superior performance of CN/WO heterostructures is ascribed to an intense localized surface plasmon resonance absorption, appropriate band alignment, and strong internal electric field. This work not only elucidates the key role of chemically bonded and plasmonic heterostructures but also paves an avenue for the rational design and construction of Z-scheme photocatalysts for solar energy conversion.